Pigmented corneal ring associated with orthokeratology in caucasians : case reports - González-Méijome, José Manuel (2012)
BACKGROUND: The aim was to report the appearance of a pigmented ring in both eyes of two patients undergoing overnight orthokeratology. METHODS: Two Caucasian patients, one male and one female, were fitted with orthokeratology lenses to correct myopia between -2.00 and -2.50 DS with Paragon corneal refractive therapy lenses worn overnight. Treatment was successful in both patients achieving uncorrected vision of 6/6 or better monocularly under high (100 per cent) and low (10 per cent) contrast conditions. RESULTS: At the six-month visit both patients presented with pigmented rings under slitlamp examination in both eyes. The location of the ring was consistent with the corneal area being flattened for myopic correction. Clinical examination was otherwise normal. CONCLUSIONS: Despite being initially reported in Asian patients from Hong Kong, a pigmented ring related to orthokeratology treatment is also present in Caucasian patients, reducing the potential role of an ethnic link. Further large-scale studies need to be done to estimate the actual incidence of this condition and the potential implications for corneal health.